2019
DOI: 10.1002/zoo.21528
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors on the foot health of captive Asian elephants (Elephas maximus) in European zoos

Abstract: Pathological lesions of feet occur frequently in captive elephant populations. To improve foot health, it is important to identify risk factors associated with such pathologies. Several previous studies have analyzed potentially influencing factors but were limited, for example, by small sample sizes. This study analyzed the relationship between 87 independent variables and the foot health score of 204 Asian elephants (Elephas maximus) in European zoos using bivariate correlation, multivariable regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The primary role of studbooks is in managing the demography of populations, and identification of trends in population demographics may highlight emerging challenges, such as an aging population or poor breeding success (Faust et al, 2006). In elephants, for example, initial research on demographics and longevity (Clubb et al, 2008) highlighted points that sparked a much wider range of studies on reproduction (Clubb et al, 2008; Freeman et al, 2009) and health (Lewis et al, 2009; Wendler et al, 2020). This sustained research focus has resulted in measurable improvements in survivorship (Scherer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The primary role of studbooks is in managing the demography of populations, and identification of trends in population demographics may highlight emerging challenges, such as an aging population or poor breeding success (Faust et al, 2006). In elephants, for example, initial research on demographics and longevity (Clubb et al, 2008) highlighted points that sparked a much wider range of studies on reproduction (Clubb et al, 2008; Freeman et al, 2009) and health (Lewis et al, 2009; Wendler et al, 2020). This sustained research focus has resulted in measurable improvements in survivorship (Scherer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, a variety of specific improvements might act in concert. For example, Wendler et al (2020) showed that foot health in European Asian zoo elephants was not related to a single factor but to a series of factors corresponding to modern husbandry. These included larger indoor and outdoor enclosures, a higher proportion of the enclosure covered by sand, larger group sizes, more free choice for elephants whether they want to be outdoors or indoors, as well as larger keeper teams.…”
Section: Discussionmentioning
confidence: 99%
“…Larger enclosures and more time spent outside and on naturalistic, soft surfaces (e.g. grass) were also correlated with better foot health, an area of particular concern for elephants [21][22][23].…”
Section: Introductionmentioning
confidence: 97%